Prevalence, aetiology and host and management factors associated with bovine mastitis in dairy cows in Zoba Anseba, Eritrea: a cross-sectional study - Redie Kidane Ghebrehawariat; Zerai Woldehiwet; Tzeggai Tesfai; Bereket Habte Imam; Yirgalem Mehari Kibrom; Abraham Debru Habte; Betiel Habte Hadgu; Filmon Berhane Kahsay; Rim Berhane Fisehaye; Samuel Haile Kahsay; Saron Yemane Yosief (BMC Veterinary Research)
Abstract From 47 dairy farms located in the Anseba Region of Eritrea, 222 cows were randomly selected for a questionnaire survey, examined for signs of clinical mastitis and milk samples tested for subclinical mastitis using the California mastitis test (CMT). Twenty cows (9%) were deemed to have clinical mastitis (CM), because they had visible clinical signs or visible changes in milk samples. Of the 202 cows tested by the CMT, 156 (77.23%) had a score of 1 or above at least in one quarter and were deemed to have subclinical mastitis (SCM). SCM was significantly more frequent in exotic breeds than in cross or indigenous breeds (p < 0.001) and cows with poor body condition compared to cows with good body condition (p = 0.025). CM was significantly more frequent in cows with a history of clinical mastitis (p = 0.004). SCM was significantly more frequent in farms that keep dung inside the compound (p = 0.004), do not milk cows with mastitis last (p < 0.01), use earthen floor (p < 0.01), do not routinely use mastitis test (p < 0.001), have intensive system of production and in farms with frequent tick infestation of the udder (p < 0.001). From 20 CM-positive and 153-SCM-positive composite milk samples tested, 29 isolates of Staphylococcus aureus, 23 Enterococcus faecium and 20 Streptococcus species, including 8 Streptococcus agalactiae were isolated. Of the 13 isolates of S. aureus tested, all were resistant to tetracycline, 11 to sulfonamides and 10 to penicillin. Two Streptococcus agalactiae isolates tested were resistant to tetracycline and penicillin.